Advancing cancer therapy: new frontiers in targeting DNA damage response - Qian, Jiekun; Liao, Guoliang; Chen, Maohui; Peng, Ren-Wang; Yan, Xin; Du, Jianting; Huang, Renjie; Pan, Maojie; Lin, Yuxing; Gong, Xian; Xu, Guobing; Zheng, Bin; et al. (Frontiers in Pharmacology, 2024)
Genomic instability is a core characteristic of cancer, often stemming from defects in DNA damage response (DDR) or increased replication stress. DDR defects can lead to significant genetic alterations, including changes in gene copy numbers, gene rearrangements, and mutations, which accumulate over time and drive the clonal evolution of cancer cells. However, these vulnerabilities also present opportunities for targeted therapies that exploit DDR deficiencies, potentially improving treatment efficacy and patient outcomes. The development of PARP inhibitors like Olaparib has significantly improved the treatment of cancers with DDR defects (e.g., BRCA1 or BRCA2 mutations) based on synthetic lethality. This achievement has spurred further research into identifying additional therapeutic targets within the DDR pathway. Recent progress includes the development of inhibitors targeting other key DDR components such as DNA-PK, ATM, ATR, Chk1, Chk2, and Wee1 kinases. Current research is focused on optimizing these therapies by developing predictive biomarkers for treatment response, analyzing mechanisms of resistance (both intrinsic and acquired), and exploring the potential for combining DDR-targeted therapies with chemotherapy, radiotherapy, and immunotherapy. This article provides an overview of the latest advancements in targeted anti-tumor therapies based on DDR and their implications for future cancer treatment strategies.